2003
DOI: 10.1038/sj.bjc.6600940
|View full text |Cite
|
Sign up to set email alerts
|

Absence of cyclin D2 expression is associated with promoter hypermethylation in gastric cancer

Abstract: Expression of cyclin D2 is absent in 30 -70% of gastric cancers. We investigated the role of promoter hypermethylation in the transcriptional silencing of cyclin D2 in five gastric cell lines and 47 primary gastric carcinomas. CpG island methylation status of the cyclin D2 gene was studied by methylation-specific polymerase chain reaction and bisulphite sequencing. RNA and protein expression was analysed by reverse transcription -PCR and Western blot, respectively. Dense methylation of cyclin D2 was detected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 26 publications
1
35
0
1
Order By: Relevance
“…As such, and being positively correlated with the metastatic potential of the tumour (this study), cyclin D2 expression may serve as an early marker for colon tumorigenesis and for prediction of clinical prognosis of colon cancer. It has been suggested that hypermethylation of the CpG islands in the cyclin D2 promoter is related to the lack of cyclin D2 protein expression in breast cancer (Evron et al, 2001), prostate cancer (Padar et al, 2003) and gastric cancer (Yu et al, 2003), while hypomethylation of the CpG islands is related to the elevated expression of cyclin D2 in gastric cancer (Oshimo et al, 2003). It is possible that the overexpression of cyclin D2 in colon cancer is also related to promoter hypomethylation.…”
Section: Discussionmentioning
confidence: 99%
“…As such, and being positively correlated with the metastatic potential of the tumour (this study), cyclin D2 expression may serve as an early marker for colon tumorigenesis and for prediction of clinical prognosis of colon cancer. It has been suggested that hypermethylation of the CpG islands in the cyclin D2 promoter is related to the lack of cyclin D2 protein expression in breast cancer (Evron et al, 2001), prostate cancer (Padar et al, 2003) and gastric cancer (Yu et al, 2003), while hypomethylation of the CpG islands is related to the elevated expression of cyclin D2 in gastric cancer (Oshimo et al, 2003). It is possible that the overexpression of cyclin D2 in colon cancer is also related to promoter hypomethylation.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic silencing of tumour-related genes due to CpG island hypermethylation has emerged as one of the most important alternations in gastric cancer development Yu et al, 2003). We have previously shown that tumour-related genes including E-cadherin, p15, and p16 were frequently methylated in gastric cancer as well as in pre-malignant gastric lesions (Leung et al, 2006), suggesting dysregulation in CpG-island methylation is likely to be involved in the early gastric carcinogenesis process.…”
mentioning
confidence: 99%
“…6,58 Whereas, loss of cyclin D2 expression by hypermethylation of its promoter region was found to be associated with tumor development in breast, lung, gastric, and pancreatic cancer, indicating that cyclin D2 might be involved in a vital tumor suppressor function in a cancer-type dependent manner. 10,[58][59][60] Our results also showed aberrant methylation of the cyclin D2 gene in all three breast cancer cell lines and correlated with silencing of the gene expression. When the cells were exposed to As 2 O 3 , the cyclin D2 promoter was partially demethylated, and cyclin D2 mRNA expression was restored.…”
Section: Tp53mentioning
confidence: 65%